An Integrative Approach Using Third-Generation Cognitive-Behavioral Therapies for Avoidant Personality Disorder. (December 2015) - Chan, Chi C.; Bach, Patricia A.; Bedwell, Jeffrey S.
Evidence-based practice emphasizes the integration of empirically supported treatments with clinical expertise and unique client characteristics. The present study describes an integrative approach using Acceptance and Commitment Therapy (ACT) and skills training adapted from Dialectical Behavior Therapy (DBT) to treat a client with avoidant personality disorder (AvPD), comorbid adjustment disorder, and self-injurious behavior. The process of matching the therapies to the client and specific techniques to symptoms and problem behaviors is described. Ongoing clinical measures indicated reductions in depression, hopelessness, and anxiety. Behavioral measures indicated remission of cutting behavior and increases in social and physical activities. Results from a 1-month follow-up suggested maintenance of gains and continued reduction in symptoms. The Minnesota Multiphasic Personality Inventory–2 (MMPI-2) profile at follow-up as compared with pre-treatment indicated significant decreases in the client's experience and perception of her symptoms. Endorsements on the Acceptance and Action Questionnaire–II (AAQ-II) at mid-treatment and follow-up suggested that the client achieved greater psychological flexibility. This case serves as evidence that individuals with AvPD and significant symptoms of anxiety and depression can be receptive to, and can benefit from, the integration of third-generation cognitive-behavioral therapies.